2020
DOI: 10.1001/jamadermatol.2020.3426
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Disease Features and Other Medical Diagnoses in Patients With Pityriasis Rubra Pilaris

Abstract: Pityriasis rubra pilaris (PRP) is a rare papulosquamous disorder that normally manifests with hyperkeratotic follicularbased papules, scaling erythematous plaques with areas of sparing, and palmoplantar keratoderma. 1 Considerable heterogeneity exists in the clinical features of PRP. Not all patients experience progression to erythroderma, and PRP is sometimes associated with a seronegative arthritis. 1,2 The prevalence of arthropathy in PRP or frequency of other known disease features such as alopecia or anh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Anhidrosis was experienced by 79.6% of PRP patients in a prior survey study 7 and similarly in 84% of our participants. Anhidrosis was associated with erythroderma in PRP in another survey study 10 and has not been studied in other forms of erythroderma so it remains unclear if alterations to sweat production are specific to PRP.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Anhidrosis was experienced by 79.6% of PRP patients in a prior survey study 7 and similarly in 84% of our participants. Anhidrosis was associated with erythroderma in PRP in another survey study 10 and has not been studied in other forms of erythroderma so it remains unclear if alterations to sweat production are specific to PRP.…”
Section: Discussionsupporting
confidence: 69%
“…PRP is a devastating skin disorder with a high burden of disease that affects multiple domains of physical and mental health and daily living. Patients with PRP have been shown to experience a lower quality of life than most other major skin disorders, including pemphigus, psoriasis, and eczema, 2 and have high rates of self‐reported depression 4,6,7 . Our aim in this mixed‐methods study was to explore the physical, mental health, and daily living impacts of PRP that may or may not be captured in other dermatology quality of life questionnaires, to help guide patients and their providers on how to best address the unique needs of people living with PRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dear Editor , Pityriasis rubra pilaris (PRP) is a rare papulosquamous condition that is comorbid with depression in 15–20% of cases 1–3 . A survey of 85 patients with PRP showed that PRP was associated with a worse quality of life (QoL) than other common dermatological conditions 4 .…”
Section: Dlqia Impaired Workb Impaired Sleepb Impaired Mobilityb Cha...mentioning
confidence: 99%
“…Lebensdekade manifestiert. Die Ätiologie ist unklar, wobei in einzelnen Fällen eine Triggerung durch Virusinfektionen (Hepatitis C, HIV), Impfungen oder Medikamente (u. a. Tyrosinkinase- und Checkpointinhibitoren), selten auch eine Assoziation mit Malignomen oder Hypothyreose beschrieben wurde [ 6 , 7 ]. Einzelne Berichte einer infektassoziierten PRP nach COVID-19-Infektion liegen vor [ 8 ].…”
Section: Fallunclassified